2014
DOI: 10.1097/moo.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

The use of mitomycin C in pediatric airway surgery

Abstract: Mitomycin C has been used for the past 16 years to inhibit pediatric airway fibroblast proliferation. Its benefit remains more hypothetical than proven and its future role remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…[ 12 ] Another study done by Gangar and Bent in 2014 concluded that mitomycin C has been used for the past 16 years to inhibit airway fibroblast proliferation but its benefit remains more hypothetical than proven and its future role remains uncertain. [ 13 ] A study by Madan et al . from a tertiary center in India concluded that mitomycin C is not an effective treatment for postintubation tracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Another study done by Gangar and Bent in 2014 concluded that mitomycin C has been used for the past 16 years to inhibit airway fibroblast proliferation but its benefit remains more hypothetical than proven and its future role remains uncertain. [ 13 ] A study by Madan et al . from a tertiary center in India concluded that mitomycin C is not an effective treatment for postintubation tracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the dose delivered to the tissues (which is concentration dependent), volume, duration of exposure, preparation method, administration, and tissue-related factors (76). Following these observations, the use of MMC was extended to the treatment of laryngeal and tracheal stenosis (77) and then esophageal stricture (78). …”
Section: Treatmentmentioning
confidence: 99%